Application of the Teams Games Tournaments Learning Model Assisted by Documentary Films on National Awakening and Youth Pledge to Improve Student Learning Outcomes - Abhi Rachma Ramadhan; Iqbal Arpannudin; Riska Nuriyani; Ismi Adnin; Daffa Fakhri Maulana (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The goal of this study was to apply the TGT (Teams Games Tournaments) learning model assisted by documentaries about national awakening and youth oaths to improve student learning outcomes. Classroom action research methods with cycle one and cycle two were used in the study. The research subjects included 33 class VII-F students (18 male students and 15 female students) and one Pancasila Education teacher at SMP Labschool Jakarta, even semester of the 2023/2024 school year. The research instrument is a test of student learning outcomes. The data analysis is based on the learning completeness criteria. In cycle one, the percentage of completeness of student learning outcomes was 36.36%. In the second cycle, the percentage of students was 81.81%. Based on the results of the study, it was concluded that student learning outcomes increased after the application of the TGT (Teams Games Tournaments) learning model assisted by documentaries about national awakening and youth oaths. Further researchers can use the TGT model assisted by other media to improve student learning outcomes.